Variation in temperature and shrinkage of Trichoderma harzianum - inoculated compost heaps and quality of compost prepared from crop and poultry wastes - VERMA, L N; RAWAT, A K; DUBEY, S B; RATHORE, G S (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1994 on decomposition in winter by heap method of composting with respect tovariation in diurnal temperature, monthly shrinkage and plant nutrients level of the compost prepared by using rice(Oryza sativa L.) straw, soybean [Glycine max (L.) Merr.] trash and their mixtures as substrates. Three levels of cagesystem poultry waste (0, 10 and 20% of the substrate) with and without the compost activator, Trichoderma harzianumwere used for compostillg. The temperature was higher at periphery than that at the centre of all the heaps up to 3 weeksof heaping, irrespective of treatments. The temperature difference was as high as 10-15Â°C in heaps prepared fromsoybean trash and 5-10Â°C in heaps prepared from rice straw. With in 48 hr of heaping maximum temperature of 52.5and 61 0 C was recorded in rice straw + soybean trash and soybean trash heaps respectively. After 3 weeks, the temperatureat periphery declined sharply and stabilized and remained almost equal to the temperature at the centre of the heaps upto 8 weeks. With time, shrinkage along the periphery was found more in rice straw heaps forming a hump structure.Activator did not cause shrinkage significantly. Nutritonally, soybean trash yielded the best quality compost. Theincreased level of poultry waste increased the nutrients status marginally. Soybean trash offered better support forAzotobacter than rice straw. Lower C : N ratio in compost from soybean trash attributed to higher population ofAzotobacter.